An overview of cognitive-behavioral management of memory dysfunction associated with chemotherapy - Ferguson, Robert J.; Martinson, Amber A. (Psicooncología, 2012)
Objective: This article summarizes current empirical support for Memory and Attention Adaptation Training (MAAT), a cognitive-behavioral treatment program that uses a compensatory strategy approach for management of late cognitive effects of chemotherapy among cancer survivors. A description of MAAT, in addition to other treatment approaches, is presented. Results: Current methods of assessing treatment gains among cancer survivors with cognitive problems who have completed programs such as MAAT need to be expanded. As such, a table of patient reported outcome (PRO) measures that may be better suited for future outcome research is proposed. Conclusions: Identifying outcome measures that accurately assess the clinical targets of MAAT and other behavioral treatments is of prime importance, as certain variables (e.g., quality of life, role strain) are not detected by neuropsychological testing in isolation. The PRO table presented in this article is intended to aid future researchers in identifying measures that can reflect quality of life improvement in response to treatments such as MAAT.